Current and Future Global Research Trends in Osteosarcoma: A Bibliometric Analysis of Surgical Strategies and Recurrence - Ridha Aswina Dalimunthe; Rhyan Darma Saputra; Rieva Ermawan (Universitas Airlangga, 2026)
Background: Osteosarcoma is the most common primary malignant bone tumor, yet comprehensive mapping of its evolving research landscape remains limited. This bibliometric analysis aims to characterize global research trends, identify thematic hotspots, and delineate emerging directions in osteosarcoma research, with a particular focus on publications related to local control, recurrence, and wide surgical margins.Methods: Publications from January 2021 to April 2025 were retrieved from the Dimensions database using the terms “osteosarcoma,” “local control,” “recurrence,” and